2015
DOI: 10.1165/rcmb.2013-0505oc
|View full text |Cite|
|
Sign up to set email alerts
|

Cigarette Smoke–Induced Damage-Associated Molecular Pattern Release from Necrotic Neutrophils Triggers Proinflammatory Mediator Release

Abstract: Cigarette smoking, the major causative factor for the development of chronic obstructive pulmonary disease, is associated with neutrophilic airway inflammation. Cigarette smoke (CS) exposure can induce a switch from apoptotic to necrotic cell death in airway epithelium. Therefore, we hypothesized that CS promotes neutrophil necrosis with subsequent release of damage-associated molecular patterns (DAMPs), including high mobility group box 1 (HMGB1), alarming the innate immune system. We studied the effect of sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 37 publications
6
58
0
Order By: Relevance
“…The smoking-induced chronic, smoldering inflammation in the lung leads to a tolerance break and altered immunity. Kearley et al recently focused on a smoking-induced IL-33-dependent proinflammatory response (100), Yuan F. et al (101) showed that cigarette smoke extract causes macrophage M2 polarization and Heijink IH et al (102) reported that cigarette smoke promotes neutrophil necrosis. In our opinion there is a need to investigate the pathobiology of cigarette smoke-inhalation—related pulmonary vascular diseases and to consider in addition to direct toxic endothelial cell effects also aberrant immune responses.…”
Section: Modifiers Of Immune Responsesmentioning
confidence: 99%
“…The smoking-induced chronic, smoldering inflammation in the lung leads to a tolerance break and altered immunity. Kearley et al recently focused on a smoking-induced IL-33-dependent proinflammatory response (100), Yuan F. et al (101) showed that cigarette smoke extract causes macrophage M2 polarization and Heijink IH et al (102) reported that cigarette smoke promotes neutrophil necrosis. In our opinion there is a need to investigate the pathobiology of cigarette smoke-inhalation—related pulmonary vascular diseases and to consider in addition to direct toxic endothelial cell effects also aberrant immune responses.…”
Section: Modifiers Of Immune Responsesmentioning
confidence: 99%
“…The release of damageassociated molecular pattern (DAMP) molecules from dying cells may amplify CS-induced vascular inflammation by promotion of additional proinflammatory responses (Sangiuliano et al, 2014). It should be noted that CS has been recently shown to promote neutrophil necrosis and the subsequent release of DAMPs including highmobility group box 1 protein (Heijink et al, 2014).…”
mentioning
confidence: 99%
“…As a consequence of the inflammation microenvironment and massive cell death induced by HPV or smoking, chronic inflammation occurs [14,26,28,29] . Increasing inflammation-related proteins, CRP and cytokines, and TNFα in the plasma of H&N cancer patients supported our assumption [12] .…”
Section: Discussionmentioning
confidence: 99%